Sistem Informasi Cash Flow dengan Menggunakan Metode Extreme Programming - Purnama, Soni Ayi (Jurnal Accounting Information System (AIMS), 2025)
CV. Yasmin Solusindo requires an information system capable of managing cash flow efficiently and accurately to support financial decision-making processes. This study focuses on the design and development of a web-based Cash Flow Information System by implementing the Extreme Programming (XP) method as a software development strategy. The choice of XP is based on its advantages in prioritizing rapid iteration cycles, intensive communication, and adaptability to changing user requirements. The XP process applied includes the stages of planning, design, coding, and testing. The developed system is able to record income and expense transactions, generate real-time cash flow reports, and reduce the risk of manual recording errors. User testing results showed a “very satisfied” satisfaction level, with scores ranging from 80% to 100%. With this system, the management of CV. Yasmin Solusindo can monitor financial conditions in real-time, enabling more effective financial planning and control